2019
DOI: 10.1002/jcp.28679
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: 9za plays cytotoxic and proapoptotic roles and induces cytoprotective autophagy through the PDK1/Akt/mTOR axis in non‐small‐cell lung cancer

Abstract: Non-small-cell lung cancer (NSCLC) is an aggressive subtype of pulmonary carcinomas with high mortality. However, chemotherapy drug resistance and high recurrence rates hinder the curative effect of platinum-based first-line chemotherapy, which makes it urgent to develop new antitumor drugs for NSCLC. 9za, a new candidate drug synthesized by our research group, has been verified with potent antilung cancer activity in preliminary experiments. However, the underlying molecular mechanism of 9za remains largely v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…In NSCLC, targeting the PDK1/PI3K/AKT pathway seemed popular in the treatment of miRNAs 39,40 and drugs. 41,42 Here, this study supported the high activation of AKT signal in NSCLC cells, accompanied with PDK1 upregulation. However, Ding et al 43 considered that miR-199a could block PDK1 expression without affecting AKT activation in NSCLC cells under hypoxia.…”
Section: Discussionsupporting
confidence: 78%
“…In NSCLC, targeting the PDK1/PI3K/AKT pathway seemed popular in the treatment of miRNAs 39,40 and drugs. 41,42 Here, this study supported the high activation of AKT signal in NSCLC cells, accompanied with PDK1 upregulation. However, Ding et al 43 considered that miR-199a could block PDK1 expression without affecting AKT activation in NSCLC cells under hypoxia.…”
Section: Discussionsupporting
confidence: 78%
“…The novel type of dual inhibitors includes a diphenylamine main frame of PD0325901, which was designated to preserve the MEK hydrophobicity, and an indolone core skeleton, which was appointed to maintain the suppressive activity against PDK1. Our previous work confirmed that 9za can induce autophagy through PDK1/Akt/mTOR signaling pathway (Liu et al, 2019b). This work further verified that 9za is indeed a dual inhibitor against MEK/ERK and PDK1/Akt signaling axes.…”
Section: Discussionsupporting
confidence: 83%
“…2A) showed the most potent anti-cancer activity among 43 new compounds in NSCLC cells so that it was selected for further research. Our previous study showed that 9za promoted autophagy via the PDK1/Akt/mTOR signal pathway and that autophagy played a pivotal role in 9za-induced cytotoxicity and pro-apoptosis in NSCLC cells (Liu et al, 2019b). However, the exact underlying mechanism of pro-apoptosis for 9za is unclear until now.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that PDK1 regulates cellular metabolism by activating the AKT/mTOR pathway (30)(31)(32). Adenoviral -PDK1 construct or adenoviral -NC construct was transduced into MC3T3-E1 cells before exposure to dexamethasone.…”
Section: Figure 4 | Upregulation Of Pdk1 Promoted the Osteogenic Abilmentioning
confidence: 99%